2.45 GHz natural polymer‐based flexible bandpass filter exploiting laser structuring. Issue 4 (14th February 2022) - Sid, Abdelghafour; Cresson, Pierre‐Yves; Joly, Nicolas; Braud, Flavie; Genestie, Benoit; Lasri, Tuami
Abstract: This article presents the realization of a bandpass filter on a flexible biopolymer substrate with a suitable fabrication process. We used copper adhesive tape and laser structuring to fabricate the filter based on a quasi‐lumped microstrip structure. The filter characteristics are a central frequency of 2.45 GHz, a bandwidth of 20%, and insertion loss of 1.2 dB. It is demonstrated that the filter's performance remains almost constant under different bending, folding, and rolling conditions. The results show that the proposed bio‐sourced polymer is a good candidate for flexible green electronics and wearable applications.